Hi,

A minor issue in the answer explanation to this problem. I am not copying out the entire explanation.

If x and y are integers such that x < y < 0, what is x - y?

(1) (x + y)(x - y) = 5

(2) xy = 6

Part of the explanation given is

As you can see, the difference between squares grows as the squares themselves get larger. The only difference between two squares that equals 5 is the difference between 4 and 9. Since x and y are both negative, this tells us that x = -3 and y = -2; therefore, x - y = -5.

The bolded portion should be

x - y = (-3) - (-2) = (-3) + 2 = -1